Genetic selection on abdominal fat content alters the reproductive performance of broilers. (25th October 2017) - Zhang, X. Y.; Wu, M. Q.; Wang, S. Z.; Zhang, H.; Du, Z. Q.; Li, Y. M.; Cao, Z. P.; Luan, P.; Leng, L.; Li, H.
Abstract : The effects of obesity on reproduction have been widely reported in humans and mice. The present study was designed to compare the reproductive performance of lean and fat chicken lines, divergently selected for abdominal fat content. The following parameters were determined and analyzed in the two lines: (1) reproductive traits, including age at first egg and total egg numbers from generations 14 to 18, absolute and relative testicular weights at 7, 14, 25, 30, 45 and 56 weeks of age, semen quality at 30, 45 and 56 weeks of age in generation 18, and fertility and hatchability from generations 14 to 18; (2) reproductive hormones at 7, 14, 25, 30, 45 and 56 weeks of age in generation 18; (3) and the relative mRNA abundance of genes involved in reproduction at 7, 14, 25, 30, 45 and 56 weeks of age in generation 18. In females, birds in the lean line laid more eggs from the first egg to 40 weeks of age than the birds in the fat line. In male broilers, the birds in the lean line had higher absolute and relative testicular weights at 7, 14 and 25 weeks of age, but lower absolute and relative testicular weights at 56 weeks of age than the birds in the fat line. Male birds in the lean line had greater sperm concentrations and larger numbers of motile and morphologically normal sperms at 30, 45 and 56 weeks of age than the birds in the fat line. Fertility and hatchability were also higher in the lean line than in the fat line. Significant differences in the plasma levels of reproductive hormones and the expression of reproduction-associated genes were also found at different ages in the lean and fat birds, in both males and females. These results suggest that reproductive performance is better in lean birds than in fat birds. In view of the unique divergent lines used in this study, these results imply that selecting for abdominal fat deposition negatively affects the reproductive performance of birds.